Designing highly luminescent aryloxy-benzothiadiazole derivatives with aggregation-induced enhanced emission. (July 2020) - Pazini, Alessandra; Maqueira, Luis; da Silveira Santos, Fabiano; Jardim Barreto, Arthur Rodrigues; Carvalho, Rafael dos Santos; Valente, Felipe Miranda; Back, Davi; Aucélio, Ricardo Queiroz; Cremona, Marco; Rodembusch, Fabiano Severo; Limberger, Jones
Abstract: A series of luminescent aryloxy-benzothiadiazole derivatives with architectures ArO-BTD-Ar' and ArO-BTD-NAr' were synthetized. The aim was to achieve a molecular design based on restriction of intramolecular rotation of the ArO- group associated to the presence of bulky aryl or N -aryl groups, which can avoid detrimental π-π stacking and favor radiative decays in the aggregated/solid state. In solution, these compounds showed fluorescence emission located in the blue to red regions with relative high fluorescence quantum yields (φFL  = 0.27–0.74). For all ArO-BTD-Ar' derivatives, emission enhancement was observed upon aggregation. The essential role of the ArO- group in the AIEEgenic ability was confirmed by comparing with Ar'-BTD-Ar' analogs. Some solid ArO-BTD-Ar' compounds displayed higher φFL than when in solution. Their aggregation-induced enhanced emission (AIEE) were corroborated by studies in water/acetone systems (I/I0 emission rations up to 7.7). Monocrystal X-ray analysis of selected compounds confirmed the twisted nature and absence of detrimental π-π stacking. The more emissive compound (φFL  = 0.83) was applied as emitting material in a green OLED structure, presenting turn-on voltage around 3.5 V and luminance up to 1200 cd m −2, with a maximum current efficiency of 5.6 × 10 −1  cd A −1  at 6.5 V. Graphical abstract: Image 1 Highlights: Aryloxy-BTD derivatives were designed aiming AIEE. Blue to red fluorescence emission with φFL  = 0.27–0.74 were observed in solution. Some solid ArO-BTD-Ar' compounds display higher φFL than when in solution. All ArO-BTD-Ar' derivatives show AIEE (I/I0 up to 7.7). The more emissive solid compound (φFL  = 0.83) was applied as emitter in a OLED.